Germinal defects of SDHx genes in patients with isolated pituitary adenoma. Issue 4 (October 2020) - Mougel, Grégory; Lagarde, Arnaud; Albarel, Frédérique; Essamet, Wassim; Luigi, Perrine; Mouly, Céline; Vialon, Magaly; Cuny, Thomas; Castinetti, Frédéric; Saveanu, Alexandru; Brue, Thierry; Barlier, Anne; et al.
Abstract : Background: : The '3PAs' syndrome, associating pituitary adenoma (PA) and pheochromocytoma/paraganglioma (PPGL), is sometimes associated with mutations in PPGL-predisposing genes, such as SDHx or MAX . In '3PAs' syndrome, PAs can occur before PPGL, suggesting a new gateway into SDHx/MAX- related diseases. Objective: : To determine the SDHx/MAX mutation prevalence in patients with isolated PAs and characterize PAs of patients with SDHx/MAX mutations. Design: : Genes involved in PAs ( AIP/MEN1/CDKN1B ) or PPGLs ( SDHx/MAX ) were sequenced in patients with isolated PAs. We then conducted a review of cases of PA in the setting of '3PAs' syndrome. Results: : A total of 263 patients were recruited. Seven (likely) pathogenic variants were found in AIP, two in MEN1, two in SDHA, and one in SDHC . The prevalence of SDHx mutations reached 1.1% (3/263). Of 31 reported patients with PAs harboring SDHx/MAX mutations (28 published cases and 3 cases reported here), 6/31 (19%) developed PA before PPGL and 8/31 (26%) had isolated PA. The age of onset was later than in patients with AIP/MEN1 mutations. PAs were mainly macroprolactinomas and showed intracytoplasmic vacuoles seen on histopathology. Conclusions: : We discovered SDHx mutations in patients bearing PA who had no familial or personal history of PPGL. However, the question of incidental association remains unresolved and data to determine the benefit of SDHx/MAX screening in these patients are lacking. We recommend that patients with isolated PA should be carefully examined for a family history of PPGLs. A family history of PPGL, as well as the presence of intracytoplasmic vacuoles in PA, requires SDHx/MAX genetic testing of patients.